POLICY IMPLEMENTATION TO ACCELERATE STUNTING REDUCTION: A QUALITATIVE STUDY - Demsa Simbolon; Tonny Cortis Maigoda; Meriwati; Solha Efrida; Yunita; Heny Widiastuti (Jurnal Administrasi Kesehatan Indonesia)
Background: The prevalence of stunting in Kepahyang Regency in Bengkulu Province is high (24.9%). Despite the policy of Accelerating Stunting Reduction or Percepatan Penurunan Stunting (PPS) outlined in Presidential Decree Number 72 of 2021, results have been suboptimal.